2009
DOI: 10.1007/s11661-009-0100-2
|View full text |Cite
|
Sign up to set email alerts
|

Stable and Unstable Flow in Materials Processed by Equal-Channel Angular Pressing with an Emphasis on Magnesium Alloys

Abstract: Magnesium alloys such as ZK60 exhibit strain softening when processed by equal-channel angular pressing (ECAP). Finite element modeling (FEM) was used to examine the flow process during ECAP with an emphasis on the importance of the strain-rate sensitivity m. The simulations show there is unstable flow and shear localization for values of m of 0 and 0.01, but the flow is stable for values of 0.05 and 0.1. The flow softening reduces the cross-sectional area of the billet and leads to an enhanced accumulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 49 publications
2
22
0
Order By: Relevance
“…However, as partial results suggest, even this eect cannot completely eliminate the emergence of cracks or other forms of failure, although they are greatly suppressed [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as partial results suggest, even this eect cannot completely eliminate the emergence of cracks or other forms of failure, although they are greatly suppressed [15].…”
Section: Introductionmentioning
confidence: 99%
“…Together with other factors, the plastic ow of the material aects both the magnitude of the imposed strain and its homogeneity and, last but not least, the disposition of the processed material to the development of cracks. The plastic ow has been researched by several authors who checked various methods of evaluation from theoretical determination [18] through experimental tests [19] up to utilization of numerical modeling which probably includes the largest number of published works especially as regards application of the nite element method (FEM) [15,20]. Most of the published works consider absence of friction as an initial condition in the process and are most frequently executed for the angle φ = 90…”
Section: Introductionmentioning
confidence: 99%
“…It is widely reported that crack-or localization-free ECAP (or other thermo-mechanical processing) of Mg alloys is possible at temperatures >200°C [9][10][11][12][13]20,21]. At these temperatures, a much higher strain rate sensitivity [2,22], significant dynamic recrystallization (DRX) activity [23] and non-basal slip activity are evident [2]. However, grain refinement is limited to the micron level, since 200°C is still relatively high for Mg alloys ($0.5T m ).…”
Section: Introductionmentioning
confidence: 99%
“…However, macro-defect-free thermo-mechanical processing of Mg-3Al-1Zn (AZ31), the most common wrought Mg alloy, is a challenge at temperatures below 200°C, due to deformation localization in combination with the formation of shear bands [20]. To the best of the present authors' knowledge, only the effects of macroscopic parameters on formability, such as the strain hardening rate and the strain rate sensitivity, have been investigated previously [20,22]. The microscopic reasons for shear band formation and localized DRX during the ECAP of Mg alloys remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, however, it is now recognized that there are often significant difficulties in the processing of magnesium-based alloys through ECAP at low temperatures due to the availability of only limited slip systems, the nature of the grain refinement process, and the development of unstable flow and segmentation. [10][11][12][13][14] By contrast, it is relatively easy to use HPT to process magnesium [15,16] and its alloys [15] at room temperature without the introduction of any cracking into the samples.…”
Section: Introductionmentioning
confidence: 99%